Effect of Storage Medium Composition on the Viability of Antagonistic Bacteria Against Stem Rot Disease - Hidayati, Nurul; Salamiah, Salamiah; Wahdah, Raihani; Razie, Fahrur; Arfianto, Fahruddin (Universitas Pendidikan Mandalika, 2026)
Stem rot is a major constraint in sweet corn and maize production, especially under humid conditions that favor pathogen development. Although antagonistic bacteria offer a sustainable alternative to chemical control, their field use is often limited by viability loss during room-temperature storage, making carrier formulation critical for shelf-life and product reliability. This study evaluated the effect of biochar–peat carrier composition on the storage viability of five antagonistic bacterial isolates for stem rot management in sweet corn. A two-factor factorial experiment (4 carrier compositions × 5 isolates) with three replications (60 experimental units) was conducted under laboratory conditions. Carriers were prepared as biochar: peat mixtures (v/v) of 3:1, 1:1, 1:3, and 100% peat. Each carrier unit (10 g) was inoculated with 1 mL bacterial suspension (≈10⁸ cfu mL⁻¹), sealed, and stored at room temperature (28–29 °C). Viability was quantified at 30, 60, and 90 days after inoculation (DAI) using serial dilution and plate counts on TSA, expressed as cfu g⁻¹. Data at 60 DAI were analyzed by factorial ANOVA including block (Group), medium (M), isolate (P), and M×P effects, followed by LSD (5%) for mean separation using SPSS 25. At 30 DAI, bacterial densities were high and did not differ among carriers, indicating comparable short-term support across media. At 60 DAI, carrier composition significantly affected bacterial density, whereas isolate and M×P interaction effects were not significant, indicating a general carrier-driven response across isolates. The biochar-rich carrier (3:1) maintained the highest mean population (8.844 × 10⁷ cfu g⁻¹). By 90 DAI, all treatments declined, yet the 3:1 carrier retained the highest density (1.089 × 10⁷ cfu g⁻¹). Overall, biochar-enriched carriers, particularly the 3:1 biochar: peat mixture, better preserved antagonistic bacterial viability under non-refrigerated storage up to 90 days.